Measuring poverty in Malaysia: Applications of distributive-sensitive poverty indices - Roslan, A.H. (Universiti Utara Malaysia, 2004)
This paper represents an attempt to seek a better way to measure poverty in Malaysia. Many studies,including government published figures employ the head-count ratio as the index of poverty. However,this measure is a narrow measure of povety. Specifically, it ignores the distribution of income among the poor, and hence has its limitation. Here, besides the usual simple head-count ratio (H) that was reported in most previous studies as well as in government documents, better poverty measures were employed - the poverty-income gap ratio (I), Sen (S), Clark, Hemming and Ulph Index (P*) and Foster, Greer and Thorbecke (FGT) indices of poverty. These indices introduce a welfare function that is sensitive to the distribution of income among the poor. Thus, they provide a richer picture of the nature of poverty and thus could be used for policy design with a greater level of confidence. Furthermore, the FGT index of poverty was decomposed to examine the contribution of different groups to total poverty. These indices were calculated using the Malaysian Family Life Survey (MFLS) data.